The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/2372732220984491
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Gender Equality by Supporting Men’s Emotional Flexibility

Abstract: Progress toward gender equality has slowed or stalled in recent years, primarily because gender stereotypes and roles are changing more quickly for women than men. Women are increasingly free to behave more like men, whereas a similar freedom for men (to behave more like women) has been slower to emerge. Expectations governing men remain rigid: They are discouraged from showing weakness/vulnerability and encouraged to assert masculinity by demonstrating strength/toughness. These expectations undermine men’s em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Notably, the concern and interest around the topic of women's underrepresentation in STEM has not been matched by a similar concern about men's underrepresentation in healthcare, early education, and domestic roles (Block et al, 2019;Croft et al, 2015;Meeussen et al, 2020). However, gender experts are now pointing at men and men's representation as a key component to advance women's place in society (Block et al, 2019;Croft et al, 2021). Gender equity will benefit men by freeing them from societal biases.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the concern and interest around the topic of women's underrepresentation in STEM has not been matched by a similar concern about men's underrepresentation in healthcare, early education, and domestic roles (Block et al, 2019;Croft et al, 2015;Meeussen et al, 2020). However, gender experts are now pointing at men and men's representation as a key component to advance women's place in society (Block et al, 2019;Croft et al, 2021). Gender equity will benefit men by freeing them from societal biases.…”
Section: Discussionmentioning
confidence: 99%
“…2003) have shown that women scored lower than men on the Nondisclosure of Imperfection subscale, thus suggesting that women are more willing to verbally express concerns and admit mistakes to others, perhaps because of social rules and expectations. Indeed, it has recently been argued that expectations governing men remain rigid across time, in that men are discouraged from showing weakness/vulnerability and encouraged to demonstrate strength (Croft, Atkinson, and May 2021). This might explain why the link between the avoidance of imperfections and psychopathology is weaker in samples mainly composed by women and seem to support previous evidence suggesting how dominant norms of masculinity can result in harm.…”
Section: Discussionmentioning
confidence: 99%
“…Female supervisors might be considered more emotionally flexible than their male counterparts (Rogier et al , 2019). They would demonstrate more flexibility in performance review meetings for longer (Croft et al , 2021). Managers from Asian cultures might be more emotionally flexible than Western ones (Ford and Mauss, 2015), with unique emotional regulation models.…”
Section: Discussionmentioning
confidence: 99%
“…Power dynamics in a performance management situation are one-directional; the manager may hold all six power bases: expert, referent, legitimate, reward, informal and coercive. It might even get more complicated if there is a female supervisor (Croft et al , 2021) and a male employee in the performance review. Similarly, an employee belonging to individualistic culture might hate the Asian female supervisor when she provides negative feedback, considering it an offender’s hurt (Croft et al , 2021; Ford and Mauss, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation